Preliminary Investigation of the Relationship between Weather Data and Hand-Foot-Mouth Disease Cases in Sarawak - Maryanne, Nicholas; Louis, Anak Denis; Jane, Labadin (2010)
This paper investigates the relationship between climate changes and the outbreak of Hand-Foot-Mouth Disease (HFMD) in Sarawak. This work is motivated by the statements made by some researchers that there may be a possibility that the outbreak of the HFMD could have a relationship with the weather. Two quantitative variables which consist of weather data and HFMD cases data are crucial for this research. The weather data comprises of the total amount of rainfall and the mean surface air temperature for the year 2000 until 2008. The evaluation of the variables’ relationship is done by using estimated weather data using spline interpolation during the outbreak of HFMD in Sarawak from year 2000 until 2008. The results obtained indicate that there exists correlation between the climate changes and the outbreak of HFMD cases in Sarawak.